Sexual exploitation of teenagers : adolescent development, discrimination, and consent law - Drobac, Jennifer Ann (Chicago : The University of Chicago Press, 2016)
When we consider the concept of sexual abuse and harassment, our minds tend to jump either towards adults caught in unhealthy relationships or criminals who take advantage of children. But the millions of maturing teenagers who also deal with sexual harassment can fall between the cracks. When it comes to sexual relationships, adolescents pose a particular problem. Few teenagers possess all of the emotional and intellectual tools needed to navigate these threats, including the all too real advances made by supervisors, teachers, and mentors. In 'Sexual Exploitation of Teenagers', Jennifer Drobac explores the shockingly common problem of maturing adolescents who are harassed and exploited by adults in their lives.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 11, 2016).
Keywords: Sexual harassment of women -- Law and legislation -- United States; Teenagers -- Legal status, laws, etc. -- United States; Sexual consent -- United States; Sexual harassment -- United States -- Prevention; Teenagers -- Sexual behavior -- United States; Law; Sexual abuse & harassment; Age groups: adolescents; Crime & criminology; Jurisprudence & general issues